Education Financing Management in an Effort to Improve the Quality of Learning in Madrasah Aliyah in Bandung District: Studies at MA Al Mua'wanah Majalaya and MA Al Jawahir Soreang - Inal Kahfi; Achmad Sanusi; Hanafiah Hanafiah; Deti Rostini (Syntax Corporation Indonesia, 2021)
Implementing education in madrasas requires financial management because it has powerful potential and is inseparable from education management. Grand Theory research uses the theory of George R. Terry, into some of the essential functions of management, into Planning (Planning), Organizing (Organizing), Actuating (Implementation), and Controlling (Supervision). The results showed that the management of education financing to improve the quality of learning in Madrasah Aliyah was still not optimal. It is proven that the quality of learning has met the standard of the learning process and seen from the teaching staff's readiness to prepare the learning process by the format of the national education quality standard. However, let's look closely at the occurrence of learning interactions between educators and students. Some educators need to increase their ability to stimulate stimulus responses from students in encouraging motivation, interest, and serious attention in developing and mastering learning materials.